Development program implementers, funders, and evaluators use A4NH tools to design, implement, and evaluate nutrition-sensitive agricultural programs seeking to empower women - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
In 2021, A4NH commissioned an external evaluation to get a sense of awareness and use of two tools – the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) and the Reach, Benefit, Empower, Transform (RBET) framework – among a target population of potential users. The evaluation found that even though the tools are still relatively new, the influence has been significant. At least 48 projects were known to be using pro-WEAI in evaluations, leveraging US$2.4 billion and reaching 10.5 million people.